Wine and landscape in the Salerno Medical School - Capone, Paola (E|C, 2020)
Wine and landscape of the Salernitana Medical School unites two great cultural containers. Avicenna puts them in relation in the Commentary of chapter X of the most famous and longest-lived text of Salerno, the Regimen Sanitatis Salernitanum (3.1 Doct. 2. chapter 8). He emphasizes the importance of wine being produced in an airy hilly area, facing south and with a temperate climate, already defining a landscape because the rows of vines then as now build landscapes.